Chest and Pelvis X-Rays as a Screening Tool for Abdominal Injury in Geriatric Blunt Trauma Patients. Issue 7 (July 2022) - Leede, Emily; Cardenas, Tatiana C. P.; Emigh, Brent J.; Brown, Lawrence H.; Teixeira, Pedro G.; Trust, Marc D.; Coopwood, Ben; Aydelotte, Jayson; Ali, Sadia; Brown, Carlos V. R.
Background: This study evaluates the utility of chest (CXR) and pelvis (PXR) X-ray, as adjuncts to the primary survey, in screening geriatric blunt trauma (GBT) patients for abdominal injury or need for laparotomy. Methods: We performed a retrospective analysis of patients 65-89 years in the 2014 National Trauma Data Bank. X-ray injuries were identified by ICD9 codes and defined as any injury felt to be readily detectable by a non-radiologist. X-ray findings were dichotomized as "both negative" (no injury presumptively apparent on CXR or PXR) or "either positive" (any injury presumptively apparent on CXR or PXR). Rates of abdominal injuries and laparotomy were compared and used to calculate sensitivity and specificity. The primary outcomes were abdominal injury and laparotomy. The secondary outcomes included mortality, ventilator days, and hospital days. Results: A total of 202 553 patients met criteria. Overall, 9% of patients with either positive X-rays had abdominal injury and 2% laparotomy vs. 1.1% and .3% with both negative ( P < .001). The specificity for any positive X-ray was 79% for abdominal injury and 78% for laparotomy. The sensitivity was 69% for abdominal injury and laparotomy. The either positive group had fewer ventilator days (.3 vs. .8, P < .0001), longer length of stay (7 vs. 5, P < .0001), and higher mortality (6% vs. 4%, P < .0001) vs both negative. Conclusion: CXR and PXR can be used to assess for intra-abdominal injury and need for laparotomy. GBT patients with either positive X-rays should continue workup regardless of mechanism due to the high specificity of this tool for abdominal injury and need for laparotomy.